Have yourself a fudgy little Christmas - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2020)
When a mysterious note leads her to a dying woman who names her friend, Frances, as her killer, fudge shop owner Allie McMurphy knows that's impossible and must wrap up this case before the trail runs cold.